Analisis Persediaan Bahan Baku pada UMKM Kare-Kare Herna Doa Ibu di Kota Bengkulu - Apriani, Denny; Afriani, Sulisti; Astuty, Kamelia (Politeknik Raflesia Press, 2025)
This study aims to analyze the inventory of ubi madu (honey cassava) as the main raw material at UMKM Kare-Kare Herna Doa Ibu in Bengkulu City by applying the Economic Order Quantity (EOQ), Safety Stock (SS), and Reorder Point (ROP) methods. Data were obtained through documentation of raw material requirements, ordering costs, and storage costs from January to July 2025. The results show that the optimal order quantity (EOQ) is 757 kg with 7 orders in 7 months. The total inventory cost using EOQ is Rp286,479.5, lower than the previous policy of Rp598,313, resulting in savings of Rp311,833.5. Furthermore, the safety stock is 490 kg and the reorder point is 673 kg. Therefore, applying EOQ significantly reduces costs by nearly 50% while ensuring raw material availability for uninterrupted production. ​​​​​​​​​​ Keywords: Inventory, EOQ,Safety Stock, Reorder Point, UMKM